Detection theory as application to the radar with a self-oscillating feedback - V. M. Kutuzov; V. N. Popov (Известия высших учебных заведений России: Радиоэлектроника, 2015)
The physical and mathematical models of radar with feedback through space and target, operating on the principle of self-oscillating system are discussed. The linear mode of fluctuations establishing is analyzed. Working detection statistics are found and detection statistics for usual radar and radar with feedback are built. Obtained characteristics compare with the corresponding characteristics of usual coherent radar. Energy stealth of the radar in standby mode and in the mode of occurrence of self-oscillations is estimated.